Acid-induced aggregation and gelation of heat-treated chia proteins - López, Débora Natalia (2021)
This work studied for the first time the acid-induced aggregation and gelation of heat-treated chia protein isolates obtained by extraction at pH 10 or 12 (CPI10 and CPI12, respectively). The aggregation state of proteins was modified during acidification. The size of the aggregates was reduced for both samples when the pH decreased but below pH 4.5 further protein aggregation took place for CPI12. Gelation of CPI12 was completed after about 30 min of acidification with glucone-δ-lactone. By contrast, this period was not enough to reach a constant value in G′ for CPI10. When gelation was ensured, confocal laser scanning micrographs from those gels revealed a coarse and irregular structure with large pores (median size of diameters: 30 μm). Instead, micrographs from CPI12 cold gels showed a more regular and interconnected network, with smaller pores (median size of diameters: 9 μm). These differences are consistent with a higher elastic behaviour ((Formula presented.) = 13.6 ± 0.1 Pa).